Iusta causa traditionis. Narava pravne podlage izročitve v luči antinomije Iul. D. 41, 1, 36 in Ulp. D. 12, 1, 18 - Žepič, Vid (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2021)
The notion of a just cause of traditio (iusta causa traditionis) has always been one of the most controversial issues of the Romanist science. The Digest contains several conflicting passages from Roman legal literature. Even the commission of Justinian`s compilers did little in Justinian’s Institutiones to harmonise the ambiguities on one of the core issues of civil law, namely whether delivery (traditio) as a fundamental legal transaction requires a valid legal basis for its effectiveness. According to the currently prevailing opinion, the traditio of classical as well as Justinian’s era was a causal transaction. The precise nature of this causality, however, remains obscure. The article focuses on the well-known antinomy between Julian’s passage D. 41, 1, 36, which presumably defends the abstract conception of traditio, and Ulpian’s apparently causal passage D. 12, 1, 18. The author provides an outline and a critique of some recent interpretations of the relationship between the antinomic passages suggesting that any attempts at harmonisation are misguided. Julian’s position seems to reflect his distinctive argumentative ingenuity and ought not to be generalised.
Keywords: lastninska pravica; obligacijsko pravo; pravna zgodovina; Rimsko pravo; stvarno pravo